Americans' Responses to Terrorism and Mass-Shooting: Evidence from the American Time Use Survey and Well-Being Module - Andrew Clark; Elena Stancanelli (Global Labor Organization (GLO), 2017)
A small but significant literature concludes that terrorism impacts the economy, although the impact of mass-shooting has not yet been addressed by economists. We compare the economic effects of two tragedies: the 2013 Boston Marathon Bombing and the 2012 Sandy Hook School Shooting. Fatal attacks are rare on any given day, and to estimate their effects we combine RDD with differences-in-differences. Using diaries of daily activities for a representative, random sample of Americans, we find a decline of over half an hour per day in average hours worked, while time spent accessing the media increased slightly. Active leisure fell after the BMB but increased after the SHSS. Daily data on emotional feelings reveal that subjective well-being fell dramatically after the BMB, and especially so for women, who are likely more averse to risk; but the findings are mixed for the SHSS. The latter induced a significant increase in meaningfulness, which was greatest for respondents with college education. We discuss these differences against economic, a priori, and drive conclusions that may be relevant for policy.
Keywords: I31; J21; J22; F52; 330; Well-being; Time Use; Terrorism